A Multi-institutional Assessment of Multimodal Analgesia in Penile Implant Recipients Demonstrates Dramatic Reduction in Pain Scores and Narcotic Usage. Issue 3 (19th December 2019) - Lucas, Jacob; Gross, Martin; Yafi, Faysal; DeLay, Kenneth; Christianson, Sarah; El-Khatib, Farouk M.; Osman, Mahdi; Simhan, Jay
Abstract: Introduction: Despite the pain associated with inflatable penile prosthesis (IPP) implantation, there has been a lack of standardized, nonopioid pain control regimens described to date. Aim: To assess the effectiveness of a multimodal analgesic regimen in patients undergoing implantation of an IPP compared with patients treated with an opioid-only regimen. Methods: A large, multicenter patient cohort undergoing IPP implantation whose pain was managed using a multimodal analgesia (MMA) protocol (preoperative and postoperative acetaminophen, meloxicam orcelecoxib, and gabapentin and intraoperative dorsal and pudendal nerve blocks) was compared with a matched cohort of patients managed via an opioid-only protocol. Both groups were compared with respect to visual analog score (VAS) and opioid usage (total morphine equivalents [TME]) in the post-anesthesia care unit (PACU), postoperative day 0 (POD0) and postoperative day 1 (POD1), and in the immediate postdischarge period. Narcotic usage on discharge and follow-up were assessed and compared. Main Outcome Measure: Postoperative pain scores and narcotic usage are the main outcome measures. Results: 203 patients were eligible for final analysis: 103 (50.7%) patients receiving MMA medication and 100 (49.3%) patients receiving opioids only. The VAS was significantly lower in the multimodal group in PACU (median 0.0 vs 2.0, P = .001), POD0 (median 3.0 vs 4.0, P = .001), and POD1 (median 3.0 vs 4.3, P = .04). Patients in the multimodal group also used fewer narcotics in PACU (median 0.0 vs 4.0 TME, P = .001), POD0 (median 7.5 vs 12.5 TME, P < .001), and POD1 (median 7.5 vs 13.5 TME, P = .01). Despite being discharged with fewer narcotics (median 20.0 vs 30.0 tablets, P < .001), a smaller proportion of patients in the MMA cohort required narcotic refills (10.7% vs 28.0%, P = .001). There were no narcotic- or MMA medication–related side effects in the entire cohort. Clinical Implications: MMA confers significant improvement in pain management while also providing a significant reduction in narcotic usage in patients undergoing implantation of IPP. Strength & Limitations: This is the 1st large multi-institutional assessment of a multimodal analgesic regimen in urologic prosthetic surgery. The analgesic regimen targets several pain pathways that provide excellent pain control throughout the recovery process. Limitations include retrospective design and lack of standardization of the nonsteroidal anti-inflammatory drug type within the multimodal analgesic regimen. Conclusion: The use of a MMA protocol significantly reduces postoperative pain measures in penile implant recipients and further reduces both inpatient and outpatient narcotic usage without any discernable side effects.